TINJAUAN IMPLIKASI KEBIJAKAN VISA REPUBLIK INDONESIA TERHADAP EKONOMI NASIONAL: REVIEW OF THE IMPLICATIONS OF THE REPUBLIC OF INDONESIA’S VISA POLICY ON THE NATIONAL ECONOMY - Ramadan, Dika Puji; Purnomo, Agung Sulistyo; Firlana, Habbi (Journal of Administration and International Development, 2025)
Abstract. The increasing global mobility of foreign citizens encourages Indonesia to continue to activate its immigration policies, especially related to visa regulations. This study aims to qualitatively examine the strengthening of the developing visa policy in Indonesia towards economic growth. Using the library study method, this study explores various academic literature, official data, and comparative studies from other countries to assess how visa policies affect international tourism, foreign investment flows, and cross-cultural interactions. The results of the study show that policies such as Visa on Arrival (VoA), Visa-Free Visits, Second Home Visas, and Golden Visas make significant contributions to economic growth. This study concludes that adaptive visa policies supported by sustainable regulations can be a strategic tool in encouraging inclusive economic growth and strengthening national resilience.Abstrak. Meningkatnya mobilitas global warga negara asing mendorong Indonesia untuk terus mengevaluasi kebijakan imigrasinya, khususnya terkait regulasi visa. Penelitian ini bertujuan untuk mengkaji secara kualitatif implikasi kebijakan visa yang berkembang di Indonesia terhadap pertumbuhan ekonomi. Dengan menggunakan metode studi pustaka, penelitian ini mengeksplorasi berbagai literatur akademik, data resmi, serta studi komparatif dari negara lain untuk menilai bagaimana kebijakan visa memengaruhi pariwisata internasional, arus investasi asing, dan interaksi lintas budaya. Hasil penelitian menunjukkan bahwa kebijakan seperti Visa on Arrival (VoA), Bebas Visa Kunjungan, Second Home Visa, dan Golden Visa memberikan kontribusi signifikan terhadap pertumbuhan ekonomi. Penelitian ini menyimpulkan bahwa kebijakan visa yang adaptif dan didukung regulasi berkelanjutan dapat menjadi alat strategis dalam mendorong pertumbuhan ekonomi inklusif dan memperkuat ketahanan nasional.